Loss calculation and thermal analysis of ultra-high speed permanent magnet motor - Zheng Li; Pengju Wang; Libo Liu; Qianqian Xu; Shuai Che; Lucheng Zhang; Shenhui Du; Hongjie Zhang; Hexu Sun (Heliyon, 2022)
The ultra-high speed permanent magnet motor (UHSPM) for hydrogen fuel cell air compressor is characterized by high speed, high motor power density, small size, and high reliability. Compared to the conventional motor, the loss per unit volume is increased and therefore the calculation of the temperature field is more important than that of conventional motors. In this paper, a UHSPM with a rated speed of 90000 r/min is designed. Firstly, a finite element (FE) model of the UHSPM is established and the losses of each part of the high-speed motor are calculated, and the calculated losses are introduced into the fluid field in the form of a heat source for motor temperature analysis. The calculated losses were introduced into the fluid field in the form of a heat source and used in the motor temperature analysis. The temperature rise was then calculated for the unidirectional and bidirectional magneto-thermal coupling (MTC) respectively. The results show that the bidirectional magneto- thermal coupling (BMTC) simulation results are about 2-3°C smaller than the experimental measured values, which can more accurately predict the motor temperature. The measurement results verify the accuracy of BMTC, and provide basic theoretical support for the subsequent cooling optimization scheme of high-speed motor.